PENGARUH PENGGUNAAN TEKNIK PRE-READING PLAN DALAM PEMBELAJARAN IPS TERHADAP HASIL BELAJAR SISWA KELAS VIII DI SMPN 2 SUMBER KECAMATAN SUMBER KABUPATEN CIREBON - Zulfah, Maulida (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Jurai Siwo Lampung, 2022)
The purpose of this study was to determine: (1) the use of the Pre-reading Plan technique in social studies learning (2) the effect of class VIII student learning outcomes at SMP Negeri 2 Sumber Cirebon (3) how much influence the use of the Pre-reading Plan technique in social studies learning had. on the learning outcomes of class VIII students at SMP Negeri 2 Sumber. In this study, the population and sample were students of SMP Negeri 2 Sumber, class VIII B, amounting to 37 students and class VIII C totaling 37 students. According to the methodology, this type of research is quantitative. Data analysis using the